Perceived Addiction as a Predictor of Smoking Cessation Among Occasional Smokers. (21st January 2016) - Chaiton, Michael; Cohen, Joanna E.; Bondy, Sue J.; Selby, Peter; Brown, K. Stephen; Ferrence, Roberta; Garcia, John M.
Abstract : Introduction: Common short screening measures of dependence that use number of cigarettes per day may not be appropriate for use in populations of occasional smokers. Aims: In this study, we investigate whether perceived addiction (PA) predicts quit attempts and successful cessation among occasional smokers. Methods: Current occasional smokers (18+) in the Ontario Tobacco Survey (OTS) longitudinal cohort study followed up every six months for up to three years. Respondents rated their self-perceived level of addiction (very vs. somewhat or not very addicted). Generalised Estimating Equation models and proportional hazard models were used to test the predictive ability of PA. Results/Findings: Occasional smokers with very high PA had a higher likelihood of reporting a quit attempt (RR: 2.49; 95% CI: 1.88, 3.30) after adjusting for demographics. Given an incident quit attempt, occasional smokers who reported being very addicted were 2.93 times more likely to relapse (95%: 2.01, 4.28). The effect of PA was independent of other predictors of smoking behaviour. Conclusions: For some, occasional smokers, smoking cessation is a difficult process that may require significant support. Asking occasional smokers about PA is an effective way to predict likely success in quitting smokers that may be easily assessed in population based, as well as in community and clinical, settings.